2012 15th International Conference on Interactive Collaborative Learning (ICL) 2012
DOI: 10.1109/icl.2012.6402179
|View full text |Cite
|
Sign up to set email alerts
|

Designing a system of interactive robots for training collaborative skills to autistic children

Abstract: Using robots to reward and stimulate children doing tasks together can be helpful in improving their social skills. Robots implemented 3 types of behavior scenarios -imitate, enhance and counteract -in a collaborative game of teaching robots perform movements shown by hand gestures. The paper presents a novel account of ASD symptoms based on the interplay of empathic concern and empathic accuracy in different personalities with and without cognitive deficits. Performance of autistic children was compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 22 publications
1
1
0
2
Order By: Relevance
“…Their study suggests that robotic systems with augmented vision may be capable of enhancing skills related to attention coordination. This confirms an earlier study of Dimitrova et al 90 where adaptive robots showed potential for educating children in various complex cognitive and social skills that eventually produce a substantial development impact.…”
Section: Motor Control/movement Patternsupporting
confidence: 90%
“…Their study suggests that robotic systems with augmented vision may be capable of enhancing skills related to attention coordination. This confirms an earlier study of Dimitrova et al 90 where adaptive robots showed potential for educating children in various complex cognitive and social skills that eventually produce a substantial development impact.…”
Section: Motor Control/movement Patternsupporting
confidence: 90%
“…Numerous investigations are being conducted on using robots with children with special needs, most of them focusing on mild to medium cases of autism, attention deficit disorder, hyperactivity, cerebral palsy, etc. (Bayon et al 2016;Charlton et al, 2005;Dimitrova et al, 2012;Huijnen et al, 2016;Kim et al, 2013). The children involved in the present study have been diagnosed with the following disorders: intellectual disability, autistic spectrum conditions, cerebral palsy, or multiple disabilities.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Играта поставя децата в различни ситуациида поставят задачи или да управляват робота, за да изпълнят задача. Освен това сценарият стимулира трите основни терапевтични задачи при деца с аутизъмимитация, едновременно насочване на вниманието и редуване в играта [18].…”
Section: фиг 2 крачещ робот Bigfootunclassified
“…Найважният параметър е т.нар. "самоиницииран социален контакт" [18,19], определян от наблюдаващия играта преподавател или родител.…”
Section: социализация чрез игра с образователен робот Bigfootunclassified